2018
DOI: 10.1177/1534735418788667
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Bortezomib-Induced Peripheral Neuropathy: Not Just for Pain

Abstract: Background: Bortezomib-induced peripheral neuropathy (BIPN) is a common and debilitating side effect. Our pilot study demonstrated that acupuncture is safe and can decrease total neuropathic symptoms. However, there is lack of knowledge in which individual BIPN symptoms benefited from acupuncture. Purpose: To characterize individual symptoms reduced by acupuncture in patients with BIPN. Methods: Patients with multiple myeloma treated with bortezomib who developed BIPN grade 2 or above, based on National Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…Focal pain spots can be treated topically with lidocaine or high-dose capsaicin patches [45]. Interestingly, complementary therapies such as acupuncture have shown a significant reduction of neuropathic pain, but also motoric impairment in BIPN Grade 2 or above [79]. In cases of relevant neuropathy, BIPN pain might be addressed by reducing subsequent bortezomib doses.…”
Section: Managing Chemotherapy-induced Neuropathic Pain (Cinp)mentioning
confidence: 99%
“…Focal pain spots can be treated topically with lidocaine or high-dose capsaicin patches [45]. Interestingly, complementary therapies such as acupuncture have shown a significant reduction of neuropathic pain, but also motoric impairment in BIPN Grade 2 or above [79]. In cases of relevant neuropathy, BIPN pain might be addressed by reducing subsequent bortezomib doses.…”
Section: Managing Chemotherapy-induced Neuropathic Pain (Cinp)mentioning
confidence: 99%
“… 30 Besides, 2 clinical trials showed a reduction in the use of analgesics and improvement in the quality of life. 31 , 32 However, the efficacy and safety of acupuncture for CIPN should be tested by well-designed and high-quality reported randomized controlled study. Further studies in investigating the mechanism of acupuncture for neuropathic pain are also needed.…”
Section: Discussionmentioning
confidence: 99%
“…One of the latest observational study conducted by Zhi et al . [ 31 ] assessed 27 patients experiencing bortezomib-induced CIPN, treated with acupuncture sessions. The patients were assessed for self-reported signs and symptoms of neuropathy using the Functional Assessment of Cancer Therapy/Gynaecologic Oncology Group-Neurotoxicity (FACT/GOG-Ntx) and neuropathic pain scale.…”
Section: Complementary and Alternative Methods In Cancer Pain Patientsmentioning
confidence: 99%